2022
DOI: 10.7759/cureus.20919
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Dilemma in Fine-Needle Aspiration Cytology: Spindle Cell/Pleomorphic Lipoma

Abstract: Pleomorphic lipoma is an uncommon, pseudosarcomatous lesion. It is characterized by the pleomorphic appearance on cytology and histology, follows a benign course, with a low rate of recurrence after complete excision, and has no risk of metastasis. Here, we describe a case of pleomorphic lipoma/spindle cell lipoma in a 41-year-old man who presented with a slow-growing mass on the inner aspect of the left thigh. On fineneedle aspiration cytology, it was reported as a cellular nerve sheath tumour followed by a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…On FNA, cellular fragments with pleomorphic spindle cells, MGCs, and fibrillary matrix within a myxoid background have been reported. [53][54][55] In an earlier study of all lipomatous tumors, many pleomorphic lipomas were misdiagnosed as anaplastic carcinoma or sarcoma. 56 These tumors are typically CD34-positive and often, but not always, lose expression of the Rb protein due to 13q alterations.…”
Section: Spindle Cell/pleomorphic Lipomamentioning
confidence: 99%
See 1 more Smart Citation
“…On FNA, cellular fragments with pleomorphic spindle cells, MGCs, and fibrillary matrix within a myxoid background have been reported. [53][54][55] In an earlier study of all lipomatous tumors, many pleomorphic lipomas were misdiagnosed as anaplastic carcinoma or sarcoma. 56 These tumors are typically CD34-positive and often, but not always, lose expression of the Rb protein due to 13q alterations.…”
Section: Spindle Cell/pleomorphic Lipomamentioning
confidence: 99%
“…They may harbor any number of floret-like giant cells in addition to the spindle cells. On FNA, cellular fragments with pleomorphic spindle cells, MGCs, and fibrillary matrix within a myxoid background have been reported 53–55. In an earlier study of all lipomatous tumors, many pleomorphic lipomas were misdiagnosed as anaplastic carcinoma or sarcoma 56.…”
Section: Giant Cell-rich Tumors Of Soft Tissuementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] With the exception of a single series, 10 the fine needle aspiration (FNA) biopsy cytopathology of SCPL has been the subject of only single or dual case studies, typically reported under the titles of either SCL [11][12][13][14][15][16][17][18][19][20] or PL. [21][22][23][24][25][26][27][28][29][30][31][32][33] In this study, we review our limited experience with the FNA cytopathology of three examples of ASPLT, which to our knowledge has not been described in the cytopathology literature previously, and compare it with the cytological features of a larger set of SCPL aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…Although morphological overlap exits between SCPL and ASPLT, SCPL typically lacks the infiltrative growth, pleomorphic lipoblasts, atypical spindle cells, and “bizarre” pleomorphic stromal/multinucleated cells found in ASPLT 2–9 . With the exception of a single series, 10 the fine needle aspiration (FNA) biopsy cytopathology of SCPL has been the subject of only single or dual case studies, typically reported under the titles of either SCL 11–20 or PL 21–33 . In this study, we review our limited experience with the FNA cytopathology of three examples of ASPLT, which to our knowledge has not been described in the cytopathology literature previously, and compare it with the cytological features of a larger set of SCPL aspirates.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of cases, pseaudosarcomatous lesions are of traumatic origin [4,7]. A recent study by Bala et al demonstrated a rare case of pleomorphic lipoma which was initially presented as a cellular nerve sheath tumor [8]. In this pseudosarcomatous lesion, only a careful examination of characteristic histopathological features allowed reaching the correct diagnosis and prevented an overtreatment in the form of extensive surgery and additional therapies [8].…”
Section: Introductionmentioning
confidence: 99%